Multivariate approach to assess the chemical composition of Italian virgin olive oils as a function of variety and harvest period. (1st December 2019) - Deiana, Pierfrancesco; Santona, Mario; Dettori, Sandro; Culeddu, Nicola; Dore, Antonio; Molinu, Maria Giovanna
Highlights: Coratina and Bosana VOOs have high phenolic content along the whole harvest period. Tonda di Cagliari and Semidana VOOs have high nutraceutical content at first harvest. Oleacein and oleocanthal increase during ripening only in Coratina variety. OPLS shows with high accuracy changes in oleacein and ligstroside aglycon content. Abstract: Fatty acids, phenolic compounds, and tocopherols of Coratina, Bosana, Semidana, and Tonda di Cagliari virgin olive oils, were measured over a 45-day harvest period. Phenolic composition was the primary factor distinguishing Bosana, Tonda di Cagliari, and Semidana, whereas fatty acids differentiated Coratina and the other cultivars. Harvest period principally influenced oleacein, oleocanthal, oleuropein and ligstroside aglycones, and flavonoids. High phenolic content was observed for Coratina (1039–688 mg/kg) and Bosana (788–592 mg/kg). A drastic decrease in phenolic content was observed in Semidana (529–134 mg/kg) and Tonda di Cagliari (507–142 mg/kg) during the harvest period. These two cultivars also had low MUFA/PUFA (6.0–4.0 and 4.9–3.2 respectively), suggesting that these varieties should be harvested earlier in the season. These results provide information to producers for improved management of the harvesting process, which is strongly affected by varietal factors.